Pemetaan Batimetri Perairan Dangkal Menggunakan Citra Satelit Sentinel-2a Dan Landsat 8 Perairan Pantai Matahari Terbit, Bali - Budaya, Ravienkha Raishasaras; Putra Dirgayusaa, I Gusti iNgurah; Darmendra, I Putu Yogi (Journal of Marine Research and Technology, 2023)
Bathymetric mapping has an important role for human activities, especially in the marine and fisheries field. However, conventional measurement of bathymetry in coastal areas is quite time consuming, high cost and difficult ship access. With the advancement of current technology, remote sensing technology using satellite imagery is believed to overcome these obstacles. In practice, there are several satellite imagery that can be used, with its own advantages and disadvantages that differ from each other. This study compared two open access  satellite imagery with different resolutions Sentinel-2A and Landsat 8 by applying Lyzenga’s algorithm to estimate depth in Matahari Terbit Beach Waters, Bali. The depth data estimated from these satellites imageries then validated with in situ measurement data collected in November 2012. To obtain the absolute depth and know the relation between the relative depth of the image and the in situ depth is carried out Inverse regression analysis. The results of the analysis using Sentinel-2A obtained an estimated absolute depth of 0 – 7.1 meters with R 2 = 0.705 and RMSE 6.165324. While the analysis using Landsat 8 obtained an estimated absolute depth of 0 – 5.5 meters with R 2 = 0.588 and RMSE 7.086484. The results showed that the data obtained using Sentinel-2A satellite imagery was better than Landsat 8’s imagery, which could be due to differences in image spatial resolution and water conditions when the images were recorded.